ANALISIS PERENCANAAN OBAT ANTIBIOTIK DENGAN METODE ABC DI INSTALASI FARMASI RUMAH SAKIT X TAHUN 2024 - Feny Febrianti; Avianti Eka Dewi Aditya Purwaningsih; Fransisca Tri Wituningtyas (Fakultas Farmasi Universitas Setia Budi, 2025)
Efficient drug procurement planning is crucial in hospital pharmacy logistics, especially for antibiotics, which consume a significant portion of the budget. This study analyzes antibiotic procurement planning at the Pharmacy Department of Hospital X in 2024 using the ABC analysis method. Out of 132 antibiotic items, 9 items (6.8%) in category A accounted for 69.32% of total costs, 22 items (16.7%) in category B for 20.41%, and 101 items (76.5%) in category C for only 10.27%. These findings support the Pareto principle and highlight the need to prioritize control over category A items. The study recommends a cost-based procurement system, integration of early warning systems, and adjustment of reorder points to achieve more rational and cost-effective antibiotic inventory management.